2017
DOI: 10.1186/s13046-017-0649-3
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of miR-193a-5p increases the chemosensitivity of prostate cancer cells to docetaxel

Abstract: BackgroundDocetaxel-based chemotherapy failure in advanced prostate carcinoma has partly been attributed to the resistance of prostate cancer (PC) cells to docetaxel-induced apoptosis. Hence, there is an urgent need to identify mechanisms of docetaxel chemoresistance and to develop new combination therapies.MethodsmiR-193a-5p level was evaluated by qPCR in prostate tissues and cell lines, and its expression in the tissues was also examined by in situ hybridization. PC cell line (PC3 cell) was transfected with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(91 citation statements)
references
References 52 publications
2
88
0
Order By: Relevance
“…The transfection used Lipofectamine 2000 (Thermo Fisher Scientific, Waltham, MA, USA) according to the manufacturer's protocols as previously described by Yang et al (28). The miR-432-5p mimics, mimic negative control (NC), miR-432-5p inhibitors, inhibitor NC, RBM5-shRNAs, b-catenin short hairpin RNA (shRNA), and negative controls were purchased from GenePharma (Shanghai, China).…”
Section: Cell Transfectionmentioning
confidence: 99%
See 3 more Smart Citations
“…The transfection used Lipofectamine 2000 (Thermo Fisher Scientific, Waltham, MA, USA) according to the manufacturer's protocols as previously described by Yang et al (28). The miR-432-5p mimics, mimic negative control (NC), miR-432-5p inhibitors, inhibitor NC, RBM5-shRNAs, b-catenin short hairpin RNA (shRNA), and negative controls were purchased from GenePharma (Shanghai, China).…”
Section: Cell Transfectionmentioning
confidence: 99%
“…All animal studies were approved by the Institutional Animal Care and Use Committee of Hebei Medical University (20080026) and were made to minimize suffering. Xenograft model was performed as previously described (28,33). Male BALB/c nude mice at 4-6 wk of age (18-22 g) were purchased from Vital River Laboratory Animal Technology (Beijing, China).…”
Section: Xenograft Animal Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…[7][8][9] Functional studies have confirmed that miRNA participates in various biological processes including cell development, differentiation, and proliferation. [15][16][17][18][19][20] Although miR-193a-5p has been proven to inhibit cell proliferation and colony formation, induce cell-cycle arrest in the G0/G1 phase and suppress tumor cell invasion, the function and the underlying mechanism of miR-193a-5p in GBM remain elusive. 14 According to previous reports, microRNA-193a-5p (miR-193a-5p) is a tumor suppressor which is lowly expressed in multiple cancers including gastric cancer, breast cancer, prostate cancer, non-small cell lung cancer, osteosarcoma, and ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%